Uncertainties of forest resources as enhanced by uncontrolled anthropogenic activities in rural Tanzania: A case of Kigosi Forest in Bukombe district - Julius Nyaombo (Talenta Publisher, 2026)
The study assessed the influence of anthropogenic activities on forest resources in Bukombe District, Tanzania. The study used a cross-sectional design and opted for a mixed-methods approach combining quantitative and qualitative methods. Data were collected through household questionnaires and interviews, and quantitative data were analysed using SPSS, while qualitative data were analysed through content analysis. The study found that some human activities degrade forests, including logging, charcoal production, firewood collection, mining, and agricultural activities, resulting in forest ecosystem deterioration, reduced ecosystem services, land degradation, and species extinction. Furthermore, the study recommended potential forest restoration practices, including afforestation, reforestation, the use of alternative sources of energy, and alternative income-generating activities with less dependence on forest resources